Correlation between Blood Lead and SGPT Levels in Parking Attendants in Kuanino Subdistrict, Kupang City - Winioliski L.O. Rohi Bire; Elisabet Christanti Kase; Agnes Rantesalu (Poltekkes Kemenkes Kupang, 2025)
Parking attendants are considered an occupational group at risk of exposure to environmental pollutants, including lead. Lead can enter the body through inhalation, ingestion, dermal contact, and ocular exposure. Chronic accumulation of heavy metals such as lead may induce hepatocellular damage, which can be reflected by increased serum glutamic pyruvic transaminase (SGPT) levels, a biochemical marker of liver injury. Elevated blood lead levels have been associated with hepatotoxic effects in several studies. This study aimed to analyze the correlation between blood lead levels and SGPT levels among parking attendants in Kuanino Subdistrict, Kota Raja District, Kupang City. An analytical observational study with a cross-sectional design was conducted using purposive sampling. Ten parking attendants were recruited. Data were obtained through interviews and laboratory examinations measuring blood lead levels and SGPT concentrations. The results showed that blood lead levels ranged from 29 µg/dL to 111 µg/dL, with a mean of 75,5 µg/dL, indicating markedly elevated levels compared to recommended safety thresholds and suggesting potential clinical risk. SGPT levels ranged from 10,2 U/L to 33,1 U/L, with a mean of 21,54 U/L. Pearson correlation analysis demonstrated no statistically significant correlation between blood lead levels and SGPT levels (p = 0,331). Future studies involving a larger sample size and additional liver function indicators are warranted to clarify this finding.